Prognostic significance of fludeoxyglucose positron emission tomography delta radiomics following bridging therapy in patients with large B-cell lymphoma undergoing CAR T-cell therapy - Ladbury, Colton; Hao, Claire; Watkins, William Tyler; Sampath, Sagus; Wong, Jeffrey; Amini, Arya; Sokolov, Karen; Yeh, Jekwon; Al Feghali, Karine A.; de Jong, Dorine; Maniyedath, Arjun; Shirvani, Shervin; et al. (Frontiers in Immunology, 2024)
Bridging radiation therapy (bRT) is increasingly being utilized prior to chimeric antigen receptor (CAR) T-cell therapy for large B-cell lymphoma (LBCL). It is unknown how the extent of cytoreduction during bRT impacts outcomes.We retrospectively reviewed patients with LBCL treated with bRT followed by CAR T-cell therapy. Metabolic tumor volume (MTV), maximum standardized uptake value (SUVmax), SUVmean, and total lesion glycolysis (TLG) were extracted from F18-fluorodeoxyglucose (FDG) positron emission tomography (PET) scans acquired prior to bRT and between completion of bRT and CAR T-cell infusion. Delta-radiomics based on changes of these values were then calculated. The association between delta radiomics and oncologic outcomes (progression free survival [PFS], freedom from distant progression [FFDP], and local control [LC]) were then examined.Thirty-three sites across 23 patients with LBCL were irradiated. All metabolically active disease was treated in 10 patients. Following bRT, median overall decreases (including unirradiated sites) in MTV, SUVmax, SUVmean, and TLG were 22.2 cc (63.1%), 8.9 (36.8%), 3.4 (31.1%), and 297.9 cc (75.8%), respectively. Median decreases in MTV, SUVmax, SUVmean, and TLG in irradiated sites were 15.6 cc (91.1%), 17.0 (74.6%), 6.8 (55.3%), and 157.0 cc (94.6%), respectively. Median follow-up was 15.2 months. A decrease in SUVmax of at least 54% was associated with improved PFS (24-month PFS: 83.3% vs 28.1%; p=0.037) and FFDP (24-month FFDP: 100% vs 62.4%; p<0.001). A decrease in MTV of at least 90% was associated with improved FFDP (24-month FFDP: 100% vs 62.4%; p<0.001). LC was improved in sites with decreases in SUVmax of at least 71% (24-month LC: 100% vs 72.7%; p<0.001). Decreases of MTV by at least 90% (100% vs 53.3%; p=0.038) and TLG by at least 95% (100% vs 56.3%; p=0.067) were associated with an improved complete response rate.bRT led to substantial reductions in MTV, SUVmax, SUVmean, and TLG. The relative extent of these decreases correlated with improved outcomes post-CAR T-cell infusion. Prospective cohorts should validate the value of interim PET following bRT for quantifying changes in disease burden and associated prognosis.